2018
DOI: 10.1177/1178223417752772
|View full text |Cite
|
Sign up to set email alerts
|

Interest of Supportive and Barrier Protective Skin Care Products in the Daily Prevention and Treatment of Cutaneous Toxicity During Radiotherapy for Breast Cancer

Abstract: Purpose:As many as 50% of patients with cancer develop acute skin reactions to some degree with radiotherapy. Proactive skin care is often recommended to minimise these skin reactions and maintain the integrity of the epidermal barrier; nevertheless, no consensual guidelines are systematically used. This multicentre, observational, prospective study evaluated the tolerability and benefit of supportive and barrier protective skin care products in preventing radiotherapy-induced skin reactions in 253 women initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 22 publications
0
30
0
2
Order By: Relevance
“…12,13 A review of randomized clinical trials revealed that there was no strong evidence that indicated differences between topical pharmacological interventions or nonpharmacological topical controls in the prevention of acute radiation dermatitis among patients with head/neck cancer undergoing radiotherapy, 14 while the combined use of various commercially available skin care products for the prevention of cutaneous toxicity during radiotherapy for breast cancer has been proven beneficial. 15…”
Section: Discussionmentioning
confidence: 99%
“…12,13 A review of randomized clinical trials revealed that there was no strong evidence that indicated differences between topical pharmacological interventions or nonpharmacological topical controls in the prevention of acute radiation dermatitis among patients with head/neck cancer undergoing radiotherapy, 14 while the combined use of various commercially available skin care products for the prevention of cutaneous toxicity during radiotherapy for breast cancer has been proven beneficial. 15…”
Section: Discussionmentioning
confidence: 99%
“…However, in a similar study, performed with breast cancer patients, 85% of patients had at least 1 skin toxicity appearing within 5 days from treatment initiation. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Lacouture, J. Choi, A. Ho, J. Leventhal, et al includes skin hygiene, moisturization, sun protection, and, if applicable, camouflage products (Table 4). [46][47][48]50 Statement 8: Skin cleansing, skin hydration, and photoprotection should be considered in cancer patients and survivors to prevent and manage cutaneous side effects before, during, and after cancer therapy.…”
Section: Photo-protectionmentioning
confidence: 99%
“…The skin care products used for patients undergoing cancer therapy should be safe, effective, free of additives, fragrances, perfumes, and sensitizing agents, and should have a near physiologic (skin surface) pH. 12,[46][47][48]50 The skincare regimen should be tailored to the individual patient, cosmetically pleasant, and easy to use (Box 4: Skincare instructions). 12,46,50 Various papers on prevention and treatment of cAEs using skincare for the specific cancer-treatments have demonstrated benefits.…”
Section: Photo-protectionmentioning
confidence: 99%